Exploring the impact of economic and sociopolitical development on people’s health and well-being: a case study of the Karanga people in Masvingo, Zimbabwe - Chirongoma, Sophia (AOSIS, 2021)
Through an exploration of the collapse of the Zimbabwean health delivery systems during the period 2000–2010, this article examines the Karanga people’s indigenous responses to utano (health and well-being). The first section explores the impact of Zimbabwe’s economic and sociopolitical development on people’s health and well-being. The next section foregrounds the ‘agency’ of the Karanga community in accessing and facilitating health care, especially their utilisation of multiple healthcare providers as well as providing health care through indigenous remedies such as traditional medicine and faith-healing. In line with the Sustainable Development Goals (SDGs), particularly SDG 3 which aspires to ensure healthy lives and promote well-being for all at all ages, the concluding section offers insights for developing an indigenous Karanga theology of utano utilising communal resources and illustrating that the concept of ‘development’ should not be confined to rigid Western development perspectives.